2018
DOI: 10.1080/13678868.2018.1429171
|View full text |Cite
|
Sign up to set email alerts
|

Advancing national human resource development research: suggestions for multilevel investigations

Abstract: AQ6 The year for "Osman-Gani and Tan, 1998" has been changed to Osman-Gani and Tan, 2000 to match the entry in the references list. Please provide revisions if this is incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 214 publications
1
24
0
Order By: Relevance
“…However, being centralized, alone, is not enough, as we can see in the case of Russia and Brazil. Garavan et al (2018) suggested that any analysis of NHRD activities might best be organized into three types: macro, meso, and micro. After their extensive review of NHRD studies, they found research at every level (but less so at the macro level), but they concluded that 'What is missing are studies that focus on all three levels of analysis simultaneously' (289).…”
Section: Introductionmentioning
confidence: 99%
“…However, being centralized, alone, is not enough, as we can see in the case of Russia and Brazil. Garavan et al (2018) suggested that any analysis of NHRD activities might best be organized into three types: macro, meso, and micro. After their extensive review of NHRD studies, they found research at every level (but less so at the macro level), but they concluded that 'What is missing are studies that focus on all three levels of analysis simultaneously' (289).…”
Section: Introductionmentioning
confidence: 99%
“…National business systems are conceptualized as the aggregation of “organizational and value orientations which characterize both the internal organization of business units and their relationship with the external environment” (Haak-Saheem & Festing, 2018, p. 3). National HRD systems place emphasis on HRD policies and practices that are unique to a particular country (Garavan et al, 2018). In contrast, an ecosystems perspective places primary emphasis on actors at multiple levels within the ecosystem and their ability to create new HRD practices.…”
Section: The Antecedents Characteristics and Implications Of Ecosysmentioning
confidence: 99%
“…The notion of an IHRD ecosystem is, we suggest, consistent with recent findings on IHRD practices. For example, research highlights the role of national and regional contexts in influencing the types of IHRD practices that are implemented (S. Kim & McLean, 2012), and in particular, the importance of national institutional forces (Garavan, Wang, Matthews-Smith, Nagarathnam, & Lai, 2018), the role of economic systems (McLean, 2017), and the choices of organizational actors (Brewster & Mayrhofer, 2012). Scholars have to date utilized a number of different approaches to understand IHRD including national human resource development (HRD) theory (McLean, 2017), varieties of capitalism theory (Allen, 2014;Hancké, Rhodes, & Thatcher, 2007), and, more recently, ecosystems theory (Baruch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is now universally recognized that the availability of skilled individuals and quality national human resources are central to future global economic competitiveness and that a country's most valued asset is its human resources (Leopold et al, 2017;Word Bank, 2018). Although NHRD has defied a univocal definition, the concept is widely acknowledged as a planned and coordinated participatory process that promote knowledge and capacity development of individuals and groups to effectively influence the processes that directly affect their lives (Kim, 2012;UNGA, 1995;Cunningham, Lynham, and Weatherly 2006;Garavan et al, 2018). As McLean and McLean (2001: 10) have since pointed out, HRD whether at organisational or national level, 'is any process or activity that, either initially or over the long term, has the potential to develop...work-based knowledge, expertise, productivity, and satisfaction, whether for 8 personal or group/team gain, or the benefit of an organization, community, nation, or ultimately the whole of humanity'.…”
Section: Nhrd and Skills Development In A Globalizing World: Towards A Postcolonial Interpretationmentioning
confidence: 99%